Implementation of Regency Regulation No. 8 of 2016 on Smoke-Free Areas: A Case Study in West Bangka Regency - Destineni; Sukrisno, Wijayono Hadi (Jurnal Penegakan Hukum dan Keadilan, 2025)
The implementation of West Bangka Regency Regulation No. 8 of 2016 concerning Non-Smoking Areas (NSA) in government office environments has faced significant challenges. Despite its intention to create a healthier workplace, data from 2023 shows that 30% of government employees still smoke in designated NSA zones. This research aims to analyze the effectiveness of this regulation and provide actionable recommendations to bridge policy gaps and enhance compliance. Using a socio-legal approach with Friedman's legal system theory, data collection involved literature reviews and in-depth interviews with key stakeholders such as law enforcement officers, supervisors, and employees. Results indicate that weak enforcement mechanisms, cultural resistance, insufficient resources, and inadequate sanctions have hindered compliance. This study highlights the interdependence of the legal system between legal structure, legal substance, and legal culture in interacting with each other. Key findings include a lack of consistent law enforcement by the civil service police unit, limited smoking cessation infrastructure, and deeply rooted smoking habits among staff. Efforts to improve must focus on integrated strategies: robust public education, sustained awareness campaigns, and stakeholder collaboration. Conclusions underscore the necessity for stronger leadership commitment and holistic approaches to promote a smoke-free culture in government offices.